This time tomorrow eaudiobook A novel. - Straub, Emma (Penguin Audio, 2022)
#1 NATIONAL BESTSELLER “The pages brim with tenderness and an appreciation for what we had and who we were. I could not have loved it more."—Ann Patchett “One of the most moving and intelligent time travel novels I have ever read. Nostalgic, wise, funny, and filled with love."—Gabrielle Zevin “The kind of book that will make you laugh, make you cry, and make you call the people you love. Exceptional."—Emily Henry What if you could take a vacation to your past?         With her celebrated humor, insight, and heart, beloved New York Times bestseller Emma Straub offers her own twist on traditional time travel tropes and a different kind of love story. On the eve of her fortieth birthday, Alice’s life isn’t terrible . She likes her job, even if it isn’t exactly the one she expected. She’s happy with her apartment, her romantic status, and her independence, and she adores her lifelong best friend. But her father is ailing, and it feels to her as if something is missing. When she wakes up the next morning, she finds herself back in 1996, reliving her sixteenth birthday. But it isn’t just her adolescent body that shocks her, or seeing her high school crush—it’s her dad, the vital, charming, forty-something version of her father with whom she is reunited. Now armed with a new perspective on her own life and his, some past events take on new meaning. Is there anything that she would change if she could?